Exogenous supplemental NAD+ protect myocardium against myocardial ischemic/reperfusion injury in swine model - Zhai, Xinrong (Am J Transl Res, 2019)
Acute myocardial infarction is one of the leading causes of deaths worldwide. Although ameliorative therapies against ischemic injury have remarkably reduced death rates among patients, they are inevitably complicated by reperfusion injury. Therefore, it is essential to explore other approaches to reduce ischemia/reperfusion injury (IRI). Modulating the levels of nicotinamide adenine dinucleotide (NAD+) is a promising therapeutic strategy against some aging-related diseases. The aim of this study was to determine the role of NAD+ in a swine model of myocardial IRI. Fourteen Bama miniature pigs were subjected to 90 min transluminal balloon occlusion, and then randomly administrated with 20 mg/kg NAD+ or saline before reperfusion. Emission computerized tomography (ECT) was performed immediately and 4 weeks after reperfusion, and the cardiac tissues were analyzed histologically. In addition, the levels of cardiac function markers and the pro-inflammatory cytokines IL-1β and TNF-α were also measured. NAD+ administration markedly reduced myocardial necrosis, enhanced glucose metabolism, and promoted cardiac function recovery. The extent of inflammation was also reduced in the NAD+ treated animals, and corresponded to less cardiac fibrosis and better ventricular compliance. Thus, NAD+ supplementation protected the myocardium from IRI, making it a promising therapeutic agent against acute myocardial ischemic disease.